UNDERSTANDING LEARNER- CHARACTERISTICS: PSYCHOLOGICAL FACTORS AND LANGUAGE DEVELOPMENT - Umurkulova Gulnoza Ismoilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Language learning is a complex and multifactorial process, in which not only intellectual, but also psychological factors play an important role. Each student has his own individual psychological portrait, and this aspect determines their success in language acquisition. Therefore, the teacher must deeply analyze the psychological characteristics of students and be able to approach them individually. Motivation is an internal or external force that encourages a student to learn a language. Integrative (interest in culture and society) and instrumental (professional or educational goals) motivations directly affect students’ language acquisition. Students with a high level of anxiety have more difficulty learning a new language. They are afraid of making mistakes and do not engage in active communication, which slows down language development.